Đánh giá tác động của việc ứng dụng AI trong giáo dục di sản cho học sinh trung học cơ sở trên địa bàn thành phố Hà Nội - Nguyễn Thị Xiêm, Nguyễn Thị Xiêm; Đỗ Phương Thảo, Đỗ Phương Thảo (Tạp chí Giáo dục, 2026)
In the context of digital transformation and the implementation of the 2018 General Education Program, the application of artificial intelligence (AI) to heritage education has become a necessary yet under - researched direction. but has not been fully researched. Theoretically, heritage education plays an essential role in creating cultural identity and civic consciousness; in practice, however, it remains relatively unattractive, underutilizes technology, and has not fully activates students’ roles in the learning process. This study has evaluated the impact of applying AI to heritage education for junior high school students in Hanoi, and affirmed the feasibility and effectiveness of this method. The results of the experimental study have demonstrated that AI contributes significantly to improving students’ capacity in all three core capacity groups: Cultural and historical awareness capacity under selflearning capacity, digital capacity under technological capacity through information technology education, creativity and interpretation capacity, critical thinking capacity under problem-solving and creativity capacity. Students not only receive information visually but also know how to create personalized products and critically evaluate digital content.